MiR-135a-5p Suppresses TBK1 and Activates NRF2/TXNIP Antioxidant Pathway in LPS-Driven ALI in Mice. (20th July 2022) - Zou, Guotao; Zeng, Yiwen; Wang, Yingjuan; Luo, Yong
Abstract : Objective . Acute inflammation and oxidative stress are present in large numbers in patients with acute lung injury (ALI). This investigation probed miR-135a-5p/TBK1 axis within ALI together with its new therapeutic target. Methods . MLE-12 cultures were treated with lipopolysaccharide (LPS) and transfected with miR-135a-5p mimics or TBK1 vector. An ALI mouse model was also established. Analysis was done on the relationships between TBK1 and miR-135a-5p. Inflammatory components, SOD, MDA, and ROS content were all assessed. Results . Obvious inflammatory lesions were observed in lung tissues of ALI mice. Overexpression of miR-135a-5p or TBK1 knockdown remarkably decreased IL-1 β, IL-6, and TNF- α serum concentrations and increased IL-10 level within lung tissues. Activated NRF2/TXNIP pathway and oxidative stress were additionally found within ALI murines, which were regulated by miR-315a-5p and TBK1. Further research revealed that miR-135a-5p negatively regulated TBK1 expression to mediate proinflammatory response and oxidative stress. Conclusion . miR-135a-5p targeted TBK1 to regulate inflammatory/oxidative stress responses in ALI. Such results might bring a new potential target for ALI treatment.